A Child in Maternal Experience: About the Poems of Joanna Mueller - Morzyńska-Wrzosek, Beata (Porównania, 2023)
A significant theme in the neo-linguistic poetry of Joanna Mueller is the individual dimension of maternity. Its poetic expressions are characterized by deepened self-reflection, search for a personal poetics, and point to transformations of postmodern aesthetics. As the poet explores the possibilities offered by language and attempts to express maternal experience, she focuses not only on the mother’s identity but also on the subjectivity of the unborn child or the infant. Describing its status, opening herself to experimenting with the phonetic and semantic wealth of language, she notes joy and care, but also uncertainty and fear that are a part of maternal experience. She reveals the potentiality of the new being, its infinitesimality, which requires concentration and permission as well as subtle gestures to ease the tensions that accompany growth. In her portrayal of building a relation with the child, Mueller emphasizes co-dependency, experiencing the child’s pricelessness and distinctiveness, gradual familiarization with what is unknown and hidden, yet so very close.